Elder and booster vaccination associates with decreased risk of serious clinical outcomes in comparison of Omicron and Delta variant: A meta-analysis of SARS-CoV-2 infection - Wu, Yanhua; Pan, Yuchen; Su, Kaisheng; Zhang, Yangyu; Jia, Zhifang; Yi, Jiaxin; Lv, Haiyong; Zhang, Lihuan; Xue, Mingyang; Cao, Donghui; Jiang, Jing (Frontiers in Microbiology, 2023)
Background: The COVID-19 pandemic brings great pressure to the public health systems. This meta-analysis aimed to compare the clinical outcomes among different virus variants, to clarify their impact on medical resources and to provide evidence for the formulation of epidemic prevention policies. Methods: A systematic literature search was performed in the PubMed, Embase, and Cochrane Library databases using the key words “Omicron” and “Delta.” The adjusted Risk ratios (RRs), Odds ratios (ORs) and Hazard ratios (HRs) were extracted, and RRs and Rate difference % (RD%) were used to interpret the risk estimates of the outcomes ultimately. Results: Twenty-eight studies were included, with 3,812,681 and 14,926,841 individuals infected with SARS-CoV-2 Delta and Omicron variant, respectively. The relative risks of hospitalization, death, ICU admission, and mechanical ventilation use after infection with the Omicron variant were all significantly reduced compared those after infection with the Delta variant (RRhospitalization=0.45, 95%CI: 0.40-0.52; RRdeath=0.37, 95%CI: 0.30-0.45; RRICU=0.35, 95%CI: 0.29-0.42; RRmechanical ventilation=0.33, 95%CI: 0.25-0.44). The reduction of both absolute and relative risks for hospitalization was more evident(RR=0.47,95%CI: 0.42-0.53；RD% =10.61, 95%CI: 8.64-12.59) and a significant increase was observed for the absolute differences in death in the elderly (RD%=5.60, 95CI%:4.65-6.55); the reductions of the absolute differences in the risk of hospitalization and death were most markedly observed in the patients with booster vaccination(RD%hospitalization=8.60, 95CI%: 5.95-11.24; RD%death =3.70, 95CI%: 0.34-7.06). Conclusion: The ability of the Omicron variant to cause severe clinical events has decreased significantly, as compared with the Delta variant, but vulnerable populations still need to be vigilant. There was no interaction between the vaccination doses and different variants.